Contributing factors to influenza vaccine uptake in general hospitals: an explorative management questionnaire study from the Netherlands - Riphagen-Dalhuisen Josien; Kuiphuis Joep CF; Procé Arjen R; Luytjes Willem; Postma Maarten J; Hak Eelko (BMC, 2012)
Abstract Background The influenza vaccination rate in hospitals among health care workers in Europe remains low. As there is a lack of research about management factors we assessed factors reported by administrators of general hospitals that are associated with the influenza vaccine uptake among health care workers. Methods All 81 general hospitals in the Netherlands were approached to participate in a self-administered questionnaire study. The questionnaire was directed at the hospital administrators. The following factors were addressed: beliefs about the effectiveness of the influenza vaccine, whether the hospital had a written policy on influenza vaccination and how the hospital informed their staff about influenza vaccination. The questionnaire also included questions about mandatory vaccination, whether it was free of charge and how delivered as well as the vaccination campaign costs. The outcome of this one-season survey is the self-reported overall influenza vaccination rate of health care workers. Results In all, 79 of 81 hospitals that were approached were willing to participate and therefore received a questionnaire. Of these, 42 were returned (response rate 52%). Overall influenza vaccination rate among health care workers in our sample was 17.7% (95% confidence interval: 14.6% to 20.8%). Hospitals in which the administrators agreed with positive statements concerning the influenza vaccination had a slightly higher, but non-significant, vaccine uptake. There was a 9% higher vaccine uptake in hospitals that spent more than €1250,- on the vaccination campaign (24.0% versus 15.0%; 95% confidence interval from 0.7% to 17.3%). Conclusions Agreement with positive statements about management factors with regard to influenza vaccination were not associated with the uptake. More economic investments were related with a higher vaccine uptake; the reasons for this should be explored further.